If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3=w/4-6
We move all terms to the left:
-3-(w/4-6)=0
We get rid of parentheses
-w/4+6-3=0
We multiply all the terms by the denominator
-w+6*4-3*4=0
We add all the numbers together, and all the variables
-1w+12=0
We move all terms containing w to the left, all other terms to the right
-w=-12
w=-12/-1
w=+12
| 4(-a+2)+2(5a-3)=2a+4(a+5) | | 4g+4(-6+3g)=1-6 | | 10x-20=-6x+12 | | -6x-4=18 | | r/2+13=20 | | 1/2x-2/3=1/6+7/12x | | 12=2p-4 | | 3x+19=9x-100 | | -4(7x+1)-4=-8+4x | | 4(45)+4(-0.75y)+3y=180 | | 4v+24=52 | | 0.7x-22=0.6 | | 3(4x+7)=1 | | 2(3x-5)-8=-(x+9)+40 | | -5x+2=20 | | -9a+-7=-23-5a | | (8x+20)=156 | | -3=4/w-6 | | -6w+9=15 | | x^2+6x=x2+6x | | -6x-7=61 | | 2(-3x-3)-(-x+1)=-5(-x+1) | | 2/3z-1/5=1 | | 10x-3=40+9 | | t=62-4*6 | | 7n-3n-8=24 | | (4x-7)/(6x-4)=0 | | 4+.75p=10+.50p | | −5(−2x−5)-x-1=-12 | | 0.5x-8=0.25x-6 | | -20=-3r+31 | | 2+x+3-5=7 |